Cholic Acid Based Anion Receptor Containing NHCarbamosulfonamide Binding Units. - Sirikulkajorn, Anchalee; Singhapha, Krittasart; Khamoad, Sasiwimol; Punyain, Wikorn; Tomapatanaget, Boosayarat (KKU Science Journal, 2017)
A synthetic receptor (S2L) based on cholic acid and possessing two NH – carbamosulfonamide binding sites at C7 and C12 positions was designed and synthesized. The binding abilities toward various anions (F-, Cl-, Br-, I-, AcO-, BzO-, CN-, H2PO4-, HSO4-, ClO4- and NO3-) were investigated using 1H-NMR spectroscopy, UV-Vis spectrophotometry, and computer simulations. Changes in the 1H-NMR spectra revealed the binding with anions occurring at the NH - carbamosulfonamide binding sites via a hydrogen bonding formation. Results from UV-Vis spectra, and optimized structures of the S2L-halide anion complexes exhibited a possibility to deprotonation at one of the NH-carbamolsulfonamide group in the case of the binding with strong basic anions (CN-, F-, AcO-, BzO- and H2PO4-). Job plot analysis indicated the formation of 1:1 host - guest complexation. The highest binding constant was obtained from CN- anion (log K = 6.08).